2010
DOI: 10.1007/978-1-4419-7185-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella catarrhalis – Pathogen or Commensal?

Abstract: Moraxella catarrhalis is an exclusively human commensal and mucosal pathogen. Its role as a disease-causing organism has long been questioned. Today, it is recognized as one of the major causes of acute otitis media in children, and its relative frequency of isolation from both the nasopharynx and the middle ear cavity has increased since the introduction of the heptavalent pneumococcal conjugate vaccine, which is associated with a shift in the composition of the nasopharyngeal flora in infants and young child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Moraxella spp. are Gram-negative bacteria that are commensals or pathogens for animals (cattle, sheep, cats, dogs, rabbits, and pigs), and Moraxella catarrhalis is a mucosal commensal or pathogen for humans (26). In silico analysis of GenBank databases revealed that a gene encoding a putative MCR-like protein was located on the chromosome of the M. catarrhalis genome, sharing 59% and 60% amino acid identity with MCR-1 and MCR-2, respectively.…”
mentioning
confidence: 99%
“…Moraxella spp. are Gram-negative bacteria that are commensals or pathogens for animals (cattle, sheep, cats, dogs, rabbits, and pigs), and Moraxella catarrhalis is a mucosal commensal or pathogen for humans (26). In silico analysis of GenBank databases revealed that a gene encoding a putative MCR-like protein was located on the chromosome of the M. catarrhalis genome, sharing 59% and 60% amino acid identity with MCR-1 and MCR-2, respectively.…”
mentioning
confidence: 99%
“…During the past decades, it has gained increasing attention as a mucosal pathogen [1,2,3] with the potential to cause upper and lower respiratory tract infections. In preschool children M. catarrhalis is the third most common cause of infective otitis media [4].…”
Section: Introductionmentioning
confidence: 99%
“…oraxella catarrhalis is an increasingly important human-specific pathogen contributing to worldwide morbidity and mortality that has transitioned from an emerging to an established pathogen (1)(2)(3). Otitis media in children is the primary cause of new antibiotic prescriptions and pediatric office visits, with M. catarrhalis accounting for 10% to 20% of acute otitis media episodes (2,(4)(5)(6).…”
mentioning
confidence: 99%